2001
DOI: 10.1177/088506660101600504
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Venous and Arterial Blood Gas Values Following Cardiothoracic Surgery in Infants and Children

Abstract: Intermittent measurement of arterial blood gases is and arterial blood gas values following cardiothoracic surgery commonly performed to assess the adequacy of in infants and children. J Intensive Care Med 2001;16:231-235. oxygenation and ventilation. Although noninvasiveThe authors retrospectively compared the correlation of pH monitors are available to assess oxygenation (pulse and pCO 2 from venous and arterial blood gases following oximetry) and ventilation (end-tidal or transcutanecardiothoracic surgery i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In this regard, various studies have been reported on children and adults to investigate the accuracy and efficacy of VBG analysis versus ABG. [5,6,[11][12][13][14][15][16] In a study carried out by Kelly, the venous and arterial pH showed a high degree of correlation (r = 0.92) and with an average difference between the samples of −0.04 units. [13] In the present study, the venous and arterial pH showed a high degree of correlation (r = 0.90) and with an average difference between the samples of 0.03 ± 0.20 which is correlated with the other studies.…”
Section: Discussionmentioning
confidence: 95%
“…In this regard, various studies have been reported on children and adults to investigate the accuracy and efficacy of VBG analysis versus ABG. [5,6,[11][12][13][14][15][16] In a study carried out by Kelly, the venous and arterial pH showed a high degree of correlation (r = 0.92) and with an average difference between the samples of −0.04 units. [13] In the present study, the venous and arterial pH showed a high degree of correlation (r = 0.90) and with an average difference between the samples of 0.03 ± 0.20 which is correlated with the other studies.…”
Section: Discussionmentioning
confidence: 95%
“…In such circumstances, it has been demonstrated that there is a strong correlation between central venous and arterial values. [1][2][3][4] However, in the early phases of resuscitation and other specific clinical scenarios, it is feasible that neither arterial nor central venous access may be present.…”
Section: Discussionmentioning
confidence: 99%
“…In the adult patient in the ICU or emergency department setting, a clinically acceptable correlation has been noted between pH, BD, and lactic acid when comparing venous and arterial samples. [1][2][3][4] However, there are no studies evaluating intraoperative correlations and limited data in the pediatric population regarding the correlation of peripheral venous and arterial values. The current study evaluated the correlation of arterial and peripheral venous values of lactic acid and BD during intraoperative care in a cohort of pediatric patients.…”
Section: Introductionmentioning
confidence: 99%